2011
DOI: 10.1021/nl104142k
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Single Crystal Domains of Few-Layer Graphene on Copper Foils

Abstract: Hexagonal-shaped single crystal domains of few layer graphene (FLG) are synthesized on copper foils using atmospheric pressure chemical vapor deposition with a high methane flow. Scanning electron microscopy reveals that the graphene domains have a hexagonal shape and are randomly orientated on the copper foil. However, the sites of graphene nucleation exhibit some correlation by forming linear rows. Transmission electron microscopy is used to examine the folded edges of individual domains and reveals they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
275
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(291 citation statements)
references
References 21 publications
(49 reference statements)
14
275
2
Order By: Relevance
“…3(b)). This is consistent with a previous study, 18 where graphene was found to preferentially nucleate along linear axes due to the initial nucleation occurring at step edges, pinning sites, or other imperfections that are linear in character. Our observations suggest that the step edge serves as carbon adatom (or cluster) sink to promote a step-flow type of growth.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3(b)). This is consistent with a previous study, 18 where graphene was found to preferentially nucleate along linear axes due to the initial nucleation occurring at step edges, pinning sites, or other imperfections that are linear in character. Our observations suggest that the step edge serves as carbon adatom (or cluster) sink to promote a step-flow type of growth.…”
Section: Resultssupporting
confidence: 93%
“…1(d) (except for the "suspended" graphene film), randomly distributed graphene domains (dark regions) can be identified beneath the top layer in a typical atmospheric pressure CVD grown sample. The top-layer graphene film is a product of the self-limited process 8 ; while the underlying domains come from the epitaxial growth mode and correspond to a multilayered structure 17,18 (see Raman spectra in Fig. 1(e)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a). A typical spectrum (red colour spectrum) shows a wider and asymmetric 2D band (full width at half-maximum of 58 cm À 1 ) with the 2D/G intensity ratio of about 0.8, which is quite similar to that of the exfoliated bilayer graphene samples with AB-stacking order [36][37][38] .…”
Section: Resultsmentioning
confidence: 51%
“…[55] Its unique structure and properties make graphene promising for a EDLC electrodes. [56] Although pure graphene sheets with high quality can be prepared by mechanical cleavage of graphite [57] or CVD method at high temperature, [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] these methods suffer from high cost, high temperature, substrate limitation, and extremely low yield. In addition, the surface of pristine graphene is so hydrophobic that pristine graphene tend to agglomerate in solvents, leading to the loss of excellent properties of monolayer graphene sheets.…”
Section: Graphene-based Flexible Edlcsmentioning
confidence: 99%